Hubungan Usia dan Paritas dengan Kejadian Perdarahan Postpartum pada Ibu Bersalin - Nur Yola Salsabila; Erina Khusnia Dewi; Kusnul Putri Yulia Wulandari; Gusriani Gusriani (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Age is a risk factor for postpartum hemorrhage, according to Rahmawati's research. An association between age and bleeding due to uterine atony was also found. Mothers aged 20 to 35 years have a 12 times higher risk of experiencing postpartum hemorrhage than mothers aged 20 to 35 years (Edah, 2019). Age parity is also a risk factor for postpartum hemorrhage. Parity refers to the number of children born to a mother (both born alive or dead). Mothers with three children are more at risk of bleeding after delivery than mothers with parity 1 to 3. The aim of this study is to analyze the relationship between age and parity and the amount of bleeding that occurs in mothers who have just given birth. The literature review method was used in this study. Various scientific articles and research reports discussing risk factors for postpartum hemorrhage are thoroughly explained. The results showed that older maternal age (above 35 years) and high parity (giving birth more than once) increased the risk of postnatal bleeding. These results suggest that mothers with these characteristics should be given special attention to reduce the risk of these complications by obtaining appropriate education, supervision during pregnancy, and appropriate birth planning.